Modeling the land surface water and energy cycles of a mesoscale watershed in the central Tibetan Plateau during summer with a distributed hydrological model. Issue 16 (22nd August 2013) - Xue, Bao‐Lin; Wang, Lei; Yang, Kun; Tian, Lide; Qin, Jun; Chen, Yingying; Zhao, Long; Ma, Yaoming; Koike, Toshio; Hu, Zeyong; Li, Xiuping
Abstract : [1] The Tibetan Plateau (TP) is the highest plateau in the world, playing an essential role in Asian monsoon development and concurrent water and energy cycles. In this study, the Water and Energy Budget‐based Distributed Hydrological Model (WEB‐DHM) was calibrated and used to simulate water and energy cycles in a central TP watershed during the summer season. The model was first calibrated at a point scale (BJ site). The simulation results show that the model can successfully reproduce energy fluxes and soil surface temperature with acceptable accuracies. The model was further calibrated at basin scale, using observed discharges in summer 1998 and the entire year of 1999. The model successfully reproduced discharges near the basin outlet (Nash‐Sutcliffe efficiency coefficients 0.60 and 0.62 in 1998 and 1999, respectively). Finally, the model was validated using MODIS land surface temperature (LST) data and measured soil water content (SWC) at 15 points within the watershed in 2010. The simulation results show that the model successfully reproduced the spatial pattern and LST means in both nighttime and daytime. Furthermore, the model can generally reproduce 15‐site averaged SWC in four soil layers, with small bias error and root mean square error. Despite the absence of long‐term discharge data for model verification, we validated it using MODIS LST and measured SWC data. This showed that the WEB‐DHM has the potential for use in poorly gauged or ungauged areas such as the TP. This could improve understanding of water and energy cycles in these areas. Key Points: Calibration and validation of distributed hydrological model Water and energy cycle in central Tibetan Plateau Use of multi‐source non‐discharge data for validation